ANALISIS PERHITUNGAN UNIT COST PADA TINDAKAN TONSILEKTOMI DENGAN METODE ACTIVITY BASED COSTING (STUDI KASUS DI RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA) - Elga Ria Vinensa; Ietje Nazarudin; Triyani Maryati (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2014)
Background: Private hospitals should strive to have the technical capability to manage and calculate costs based on the condition that both hospitals and facilities that can use the Indonesian Case Based Group (INA CBG) appropriately. RS PKU Muhammadiyah Yogyakarta as one of the private hospitals that participate and support the government's program of the Sistem Jaminan Sosial Nasional.Calculating the unit cost of a tonsillectomy was done as a study of the correspondence between the cost of services and a health claim Methods:The study was a descriptive qualitative case study design. Tonsillectomy unit cost calculation using activity based costing (ABC) with the goal difference obtained unit costs plus a margin to claim CBG INA in 2012. Result: Based on the calculation, the unit cost of services tonsillectomy with activity-based costing method is Rp. 2.265.732. ABC unit cost calculations result in a greater cost than the claims of INA CBG so get the difference in cost of Rp. 785.034. Conclusions: There is a negative difference between the calculation of service bi tonsillectomy ABC method with INA CBG claim. So that needs to be done by the hospital cost efficiency.